Electronic Proposal Box for Process Improvement - An interactive communication through web - Hameed, Farhan; Zaheer, Hamza (My University, 2012)
A rapid advancement in technology has influenced the manufacturing industry to make right decisions at right time for their growth. To maintain a steady market share in a competitive environment, companies have to focus on customer needs. Also they have to think ahead to be a leader in introducing innovative features with better quality product. To find out the key areas for improvement we have applied Lean thinking in a process of product development. A research is conducted in the manufacturing industry consisting of design engineers, process owners and research analysts with ten different manufacturing companies. The research pointed out the delays in communication between the design engineers and process owner at the time of process development. To communicate effectively a need for improvement in communication has emerged out with a simple and easy to use collaborative platform for design engineers and process owners. We performed a case study on one of the automotive company to find out the root causes of delays and then gather requirements for system development. A development phase started with three main parts; a WIKI to maintain the versions of the processes with a WYSIWYG (what you see is what you get) interface for effective communication, a profile card and a dashboard to give the overall picture about the evaluation and usage of a process to a process owner. A development step followed the extreme programming(XP) process for software development and an iterative way is used for process evaluation. This approach helped in evaluating a process during process development based on the results of a process when tested on a test bed. This evaluation step led towards the standardization of a process. Eventually it has reduced the response time of a process owner to give spontaneous feedback about the process to involved design engineers. A collaborative environment is not only provided with textual information but also with audio and visual information which are easy to understand. It also makes the communication more effective and efficient. A developed system has fulfilled all the baseline requirements and well appreciated by the customers as a first successful step towards process improvement. But a disinclination was found to learn a new system in a start which indicated some new requirements for future improvements in the system.
Keywords: Data- och informationsvetenskap; Computer and Information Science